Immediate Dentin Sealing: A Literature Review - Samartzi TK; Papalexopoulos D; Sarafianou A; Kourtis S (Dove Medical Press, 2021)
Theodora-Kalliopi Samartzi,1 Dimokritos Papalexopoulos,2 Aspasia Sarafianou,2 Stefanos Kourtis2 1Private Dentistry Practice, Athens, Greece; 2Department of Prosthodontics, National and Kapodistrian University of Athens, Athens, GreeceCorrespondence: Dimokritos PapalexopoulosDepartment of Prosthodontics, National and Kapodistrian University of Athens, Athens, GreeceEmail dimpapalex@hotmail.comPurpose: The immediate application of a dentin-bonding agent after tooth preparation and before impression-taking (immediate dentin sealing [IDS]) has been suggested to provide several advantages concerning bacterial microleakage, hypersensitivity, and bonding quality. We reviewed the literature and clarified certain aspects related to each step of IDS application.Materials and Methods: The search strategy comprised an electronic research in MEDLINE, Cochrane, Ovid and Scopus for studies published from January 1990 to December 2020 regarding the IDS technique and including both in vitro and clinical studies.Results: After exclusion of irrelevant or duplicate articles, 88 articles focusing on aspects of the IDS technique were assessed. IDS seems to be advantageous with regard to bond strength, gap formation, bacterial microleakage, and dentin hypersensitivity. However, issues arising from interaction with impression materials, the provisional phase, and conditioning methods before cementation require further investigation.Conclusion: There are no documented reasons preventing clinicians applying IDS in their everyday practice. On the contrary, the presented technique seems to be beneficial in certain aspects regarding indirect restorations.Keywords: IDS, indirect restorations, restorative dentistry, review